Environmental influences on childhood allergies and asthma — The Farm effect. Issue 6 (3rd June 2022) - Frei, Remo; Heye, Kristina; Roduit, Caroline
Abstract: Asthma and allergies are major health problems and exert an enormous socioeconomic burden. Besides genetic predisposition, environmental factors play a crucial role in the development of these diseases in childhood. Multiple worldwide epidemiological studies have shown that children growing up on farms are immune to allergic diseases and asthma. Farm‐related exposures shape children's immune homeostasis, via mediators such as N‐glycolylneuraminic acid or arabinogalactan, or by diverse environmental microbes. Moreover, nutritional factors, such as breastfeeding or farm milk and food diversity, inducing short‐chain fatty acids‐producing bacteria in the intestine, contribute to farm‐related effects. All farm‐related exposures induce an anti‐inflammatory response of the innate immunity and increase the differentiation of regulatory T cells and T helper cell type 1. A better understanding of the components of the farm environment, that are protective to the development of allergy and asthma, and their underlying mechanisms, will help to develop new strategies for the prevention of allergy and asthma.